Building defect: The implication of plants on building elements / Nurul Fatehah Md Nadzri - Md Nadzri, Nurul Fatehah (Faculty of Architecture , Planning and Surveying, 2015)
Damage often occurs as a result of the plant. But this issue did not receive serious attention from all parties on whether the owner of the building or the maintenance.The study covers made in this thesis, the researcher would like to see how trees element can cause damage to the building elements, to investigate the damage due to plants on building surrounding in Education area and to evaluate individual awareness on the implication of plants on building elements.When trees are planted too close to a building, the roots of them are causing damages to that building in both direct and indirect ways. In many cases, these subterranean problems go unnoticed, until cracks appear on surfaces. The remedial works for such cases can be always difficult and expensive. This research was carried out to identify the causes and effects of not using the safe planting distances and then it is extended with a detail survey to find safe distances using three categories of trees, which are most common in Malaysia. It was noted that the direct damages to civil structures are very common here in Malaysia. It was observed that the damage from large or matured tree like Lime, Ash and etc. is much greater than other trees. Therefore, its’ safe planting distance is around 10 meters and above.Safe planting distances for Tamarind and Royal Poinciana are in a range between 6 to 7 meters. For Jack and Mango tree, it is about 4 to 5 meters. So these safe planting distances has represented numerically in this report.